Eco-biocompatibility of chitosan coated biosynthesized copper oxide nanocomposite for enhanced industrial (Azo) dye removal from aqueous solution and antibacterial properties. (1st August 2020) - Sathiyavimal, Selvam; Vasantharaj, Seerangaraj; Kaliannan, Thamaraiselvi; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Synthesis of an-eco-friendly and non-toxic chitosan coated copper oxide nanoparticles (CS-CuO nanocomposite). CS-CuO nanocomposite was showed potential antibacterial and degradation properties. CS-CuO nanocomposite acts as a good reducing and capping agent of chitosan macromolecules. Abstract: In the present study, the biogenic synthesis of an ecofriendly and non-toxic chitosan (CS) coated copper oxide NPs (CS-CuO nanocomposite) using Psidium guajava aqueous leaf extract. The biogenic synthesized CS-CuO nanocomposite was characterized by using UV–vis spectroscopy analysis (UV-Vis), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and Field emission scanning electron microscopy with energy dispersive X-ray spectroscopy (FE-SEM-EDS), Dynamic light scattering (DLS), and Transmission electron microscopy (TEM). The prepared CS-CuO nanocomposite was evaluated for antibacterial activity by agar well diffusion method as well as minimum inhibitory concentrations (MIC) were assessed against both Gram-positive Streptococcus pneumoniae, Staphylococcus epidermidis and Gram-negative Escherichia coli, Proteus mirabilis with good inhibition effects on Gram-negative bacteria than the Gram-positive bacteria. The interaction of the CS-CuO nanocomposite with the bacterial membrane was visually observed by confocal laser scanning microscopy and the live/dead cells were differentiated by treatment with acridine orange and ethidium bromide dyes.